Arc volcano of Japan generation of continental crust from the mantle - Yanagi, Takeru; SpringerLink (Online service (Berlin New York Springer, 2011)
This book presents an analysis of our current knowledge on the origin of the Earth?s continental crust. There are two aspects to consider: tectonic and igneous processes. Tectonic aspects include sedimentary accretion, terrane accretion, and continental collision at continental margins, in association with plate subduction. These processes result in the formation of large mountain belts, the building up of which literally grows the continents. However, these tectonic aspects are concerned with material recycling within the crust, and hence do not contribute to volumetric growth of continental crust. Igneous processes concern separation of continental crust from the mantle and result in the volumetric growth of continental crust. Therefore, the main focus of this book is to systematically examine why and how the Earth?s continental crust forms, by evaluating magmatic processes at island arcs where new continental crust
Chapter 1  Continental Crust and Granitic Plutons -- Chapter 2  Chemical Composition of Continental Crust and the Primitive Mantle -- Chapter 3  Origin of Magmas of the Bowen?s Series -- Chapter 4  Search for the Formation Mechanism of Continental Crust -- Chapter 5  Differentiation Mechanism of Magma at Arc Volcanoes -- Chapter 6 Configuration and Dynamics of the Magma Chambers Beneath Arc Volcanoes -- Chapter 7  Island Arc Volcanic Rocks and the Upper Continental Crust -- Chapter 8  Volcanic Arcs and Oute
Electronic reproduction.
Keywords: Continental crust .; Island arcs; Electronic books